Pembinaan Spiritual dalam Meningkatkan Akhlak Siswa BASIS (Barisan Siswa) di SMPN Kabupaten Sumedang - Rifa Tri Rizqillah; Sobarna, Ayi; Khambali (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research is motivated by the emergence of gang phenomena in schools. It is observed that some students are involved in the BASIS gang, engaging in various forms of delinquency such as drinking alcohol, using drugs, smoking, vandalizing vehicles, and tattooing. In response, the school is striving to improve the morals of BASIS students by involving Islamic Religious Education (PAI) teachers in a special program called spiritual guidance. The research employs a case study method with a qualitative approach. Data collection techniques include three stages: observation, interviews, and documentation. The research findings indicate that: (1) PAI teachers facilitate BASIS students in building a stronger relationship with God through spiritual guidance activities such as prayers before activities, Dhuha prayer, congregational Dzuhur prayer, and Iqro learning. Additionally, teachers provide teachings on the concept of Allah’s compassion and belief in God’s existence, and conduct personal approaches through sharing sessions. (2) PAI teachers assist BASIS students in exploring a deeper meaning of life by delivering lectures on life’s purpose, human creation, the concept of sincerity, and the meaning of prayer. Besides lectures, teachers also involve students in additional religious activities such as girls’ gatherings. (3) To enhance the spiritual awareness of BASIS students at SMPN,PAI teachers encourage them to engage in charitable giving, honesty, dialogue, and dhikr (remembrance of God). Teachers also set examples and impose penalties and warnings for students involved in conflicts to deter them from misbehavior. Abstrak. Penelitian ini dilatarbelakangi oleh munculnya fenomena geng di sekolah. Hal ini terlihat ada beberapa siswa yang terlibat kedalam geng BASIS dengan berbagai macam kenakalan yang dilakukan seperti siswa mabuk, mengonsumsi obat, merokok, nge BM (Berhentiin Mobil), siswi yang bertato dan sebagainya. Dengan adanya geng ini pihak sekolah melibatkan guru PAI dalam program pembinaan khusus yang disebut pembinaan spiritual. Metode yang digunakan pada penelitian ini adalah metode studi kasus dengan pendekatan kualitatif. Teknik pengumpulan data pada penelitian ini menggunakan observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukan (1) Upaya guru PAI memfasilitasi siswa BASIS dalam membangun hubungan yang lebih dengan Tuhan melalui pembinaan spiritual dilakukan melalui berbagai kegiatan ibadah seperti doa sebelum kegiatan, shalat Dhuha, shalat Dzuhur berjamaah, dan belajar iqro, pemberian materi akidah dan pendekatan personal. (2) Upaya guru PAI membantu siswa BASIS dalam proses pencarian makna hidup yang mendalam, guru memberikan siraman rohani yang mencakup tujuan hidup, penciptaan manusia, konsep ikhlas, dan makna shalat. Selain itu, guru juga melibatkan siswa dalam kegiatan keagamaan tambahan seperti kegiatan keputrian. (3) Upaya guru PAI dalam meningkatkan kesadaran spiritual siswa BASIS di SMPN Kabupaten Sumedang, guru membiasakan mereka untuk berinfak, berkata jujur, berdialog, dan berdzikir. Guru juga memberikan teladan serta menetapkan hukuman dan ancaman untuk siswa yang terlibat dalam konflik, guna memberikan efek jera.